Exploring Tourists’ Landscape Preferences in Indonesia Through Keyword Analysis - Pamungkas, Muhamad Ramdani; Wulandari, Endang (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
This study examines tourists’ landscape preferences in Indonesia through the analysis of descriptive words used to express perceptions of natural and urban environments. Using an exploratory qualitative approach, open-ended responses were collected from domestic and international tourists who described what they found appealing and unappealing in various landscapes. Text data were cleaned, coded, and analyzed using frequency counts and wordcloud visualization to identify dominant patterns. The results reveal that natural landscapes are primarily associated with positive terms such as beautiful, green, water, mountain, and calm, indicating that visual harmony, natural elements, and tranquility are central to their appeal. Conversely, urban landscapes are linked to words like building, crowded, traffic, and residential, suggesting that the dominance of man-made structures and congestion reduces aesthetic appreciation. These findings confirm that tourists generally prefer open, natural, and visually balanced settings over dense urban environments. The study contributes to understanding how tourists linguistically express visual and emotional responses to landscapes, providing insights into the patterns of landscape appreciation within Indonesia’s diverse tourism context. The results can guide destination managers in emphasizing natural features and improving urban environments to align with visitor preferences.